2020
DOI: 10.1159/000507852
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attention-Deficit/Hyperactivity Disorder and Quality of Life in High-Dose Benzodiazepine and Related Z-Drug Users

Abstract: Background: Problematic high-dose benzodiazepine (BZD) and related Z-drug use for a long period is a substance use disorder previously found to be associated with adult attention-deficit/hyperactivity disorder (ADHD) and worse quality of life (QoL). Whether adult ADHD impacts QoL in high-dose BZD/Z-drug users has not been explored. Aim: The aim of the study was to explore the impact of adult ADHD on QoL in high-dose BZD and related Z-drug users. Methods: We recruited 393 patients (205 men and 188 women) consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
(99 reference statements)
2
9
0
Order By: Relevance
“…Adult ADHD symptoms were overrepresented in highdose BZD/Z-drug users, in that 39.4% of our sample was positive to adult ADHD screening with the ASRS v1.1 Symptoms Checklist Part A. This finding is in keeping with our previous report (Lugoboni et al 2020b), and in accordance with studies in other SUD patients (van de Glind et al 2013;Katzman et al 2017), where the prevalence of adult ADHD symptoms was reported up to 8 times higher than the general population (Volkow and Swanson, 2013). At variance with the general population (Chung et al 2019), demographic variables did not differ between ADHD + and ADHD− groups, probably because of the limited age range of our sample.…”
Section: Adult Adhdsupporting
confidence: 92%
See 3 more Smart Citations
“…Adult ADHD symptoms were overrepresented in highdose BZD/Z-drug users, in that 39.4% of our sample was positive to adult ADHD screening with the ASRS v1.1 Symptoms Checklist Part A. This finding is in keeping with our previous report (Lugoboni et al 2020b), and in accordance with studies in other SUD patients (van de Glind et al 2013;Katzman et al 2017), where the prevalence of adult ADHD symptoms was reported up to 8 times higher than the general population (Volkow and Swanson, 2013). At variance with the general population (Chung et al 2019), demographic variables did not differ between ADHD + and ADHD− groups, probably because of the limited age range of our sample.…”
Section: Adult Adhdsupporting
confidence: 92%
“…In keeping with previous studies, all SF-36 dimensions were worse in high-dose BZD/Z-drug users than the general population (Tamburin et al 2017b), and worse in ADHD+ than ADHD− groups (Lugoboni et al 2020b). GHQ-12 scores did not differ according to the positivity to adult ADHD screening that is in contrast to a previous report from our group (Tamburin et al 2017b).…”
Section: The Influence Of Adult Adhd and Cognition On Qolsupporting
confidence: 90%
See 2 more Smart Citations
“…2,6 Lastly, regarding zolpidem's hazardousness, we would like to report the fact that zolpidem was significantly preferred by addicts with a positive ADHD test result. 5 These data should be kept in mind by institutions and services that study and handle neurodevelopmental issues.…”
mentioning
confidence: 99%